Starting a New Residency—The Early Years. (29th January 2023) - Stanisce, Luke
Abstract: The social dimensions of residency are as essential as the scientific ones, particularly when starting a new program. Privileged to be the first‐ever trainee in a newly accredited residency program, this reflection details the particulars defining my experience. In an attempt to balance humility with accomplishment, the following offers unique observation and insight on the many aspects we all share in training, in the aim of contributing something meaningful to them.